Pelindungan Data Pribadi Anak Yang Berhadapan Dengan Hukum di Dunia Siber - Anggraeni, Rinastiti Dwi; Alsabilla, Fadilla Putri; Kameo, Jeferson (Universitas Semarang, 2024)
This research aims to provide a perspective on the protection of the personal data of children which are in conflict with the law in cyberspace, stipulated in Article 19 jo 97 of Law No. 11 of 2012 on the Juvenile Criminal Justice System. It is hoped that this research will provide a new perspective on the role and responsibility of judges in protecting children's personal data in cyberspace, which is not legally but morally defined. The legal issue of this research is the vagueness of the meaning of the phrase